2012
DOI: 10.3389/fnhum.2012.00196
|View full text |Cite
|
Sign up to set email alerts
|

Visual cognition during real social interaction

Abstract: Laboratory studies of social visual cognition often simulate the critical aspects of joint attention by having participants interact with a computer-generated avatar. Recently, there has been a movement toward examining these processes during authentic social interaction. In this review, we will focus on attention to faces, attentional misdirection, and a phenomenon we have termed social inhibition of return (Social IOR), that have revealed aspects of social cognition that were hitherto unknown. We attribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 127 publications
1
40
0
Order By: Relevance
“…Such studies have led to some revisions of what is known about visual attention (see Skarratt, Cole, & Kuhn, 2012, for an extensive review). For instance, gaze cues were for a long time assumed to be unable to induce inhibition of return (IOR; Posner & Cohen, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…Such studies have led to some revisions of what is known about visual attention (see Skarratt, Cole, & Kuhn, 2012, for an extensive review). For instance, gaze cues were for a long time assumed to be unable to induce inhibition of return (IOR; Posner & Cohen, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…A final concern for this field, as suggested by research on gaze selection and joint action, is the need to understand attention to action in ecologically valid contexts (see Skarratt et al, 2012). This approach has the ability to underscore the pervasiveness of effects observed in the lab yet also reveal subtleties that were not previously apparent.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Taken in conjunction with the findings of Welsh, Ray, et al (2009), these findings suggest that when visual transients are restricted, the effect is sensitive to manipulations of social or interactive context, as well as being dissociable in populations with atypically developing traits in social interaction. This has led to the term social IOR being applied to the between-person IOR effect (Skarratt, Cole, & Kuhn, 2012), implying an IOR effect that is necessitated by some level of social interaction.…”
Section: Social Inhibition Of Returnmentioning
confidence: 99%
“…Furthermore, the fact that only a few studies have shown IOR induced by central cues may suggest that many failed to find such an effect and consequently did not submit the work for publication. However, it is becoming clear from the dozens of experiments published to 10 date that IOR can be generated robustly and more generically with a central cue if the cue is a real individual that interacts with the participant, an effect termed 'between-participant' IOR (Welsh et al, 2005; or 'social' IOR (Skarratt, Cole, & Kingstone, 2010;Skarratt, Cole, & Kuhn, 2012).…”
Section: Inhibition Of Returnmentioning
confidence: 99%